Effect of Fundamental Factors, Investment Opportunity Set and Company Growth on Stock Prices at Mediation By Decision on Plantation Sector Investment on the Indonesia Stock Exchange - Adi Hasan Ragil Saputra (Jurnal Akuntansi, 2019)
The share price of the plantation sector during the period of 2013 - 2017 is one of the sectors that have growth negative (Financial Market Update, 2017). This study uses a sample of plantation sector companies listed on the Indonesia Stock Exchange during 2013-2017 with a sampling technique that is purposive sampling and analyzed with structural equation modelling (SEM) . The results of the study show that the fundamentals of stock prices both directly and indirectly are significant. IOS to share prices, both directly and indirectly, are significant. While the company's growth in stock prices both directly and indirectly are not significant. This is because the growth of plantation sector companies is more dominantly influenced by external factors outside of management and company conditions. Investment decisions have a significant effect on stock prices. Investment decisions have a significant effect intervening the effect of fundamental variables on stock prices. Investment decisions also significantly influence intervening the effect of IOS variables on stock prices. While investment decisions have no significant effect in intervening the company's growth in stock prices.